(untitled) (Eurasian Journal of Ecology, 2024)
The article presents the results of studies of the soil cover of plant communities with the participation of Rosa potentilliflora Chrshan. et. M.Pop. in the conditions of the spruce belt of the central part of the Trans-Ili Alatau and its eastern slopes of the Toraigyr and Syugaty mountains. The research work has fully demonstrated that the formation of soils, climate and vegetation cover of the lands of the studied zone in connection with their lying above sea level is directly related to the zonal pattern of high-altitude belts.Here the soil types, vegetation composition, morphological characteristics, chemical and mechanical composition of plant communities in which the plant Rosa potentilliflora Chrshan. et. M.Pop is found are determined. From the study areas, chernozem types were identified in the conditions of the spruce belt in the central part of the Trans-Ili Alatau and its eastern slopes of the Toraigyr and Syugaty mountains. Based on their mechanical composition, medium clayey, light clayey and heavy clayey soils are distinguished. The soil of plant communities is very fertile, rich in humus, the amount of salts that quickly dissolve in water is very small, practically absent. It is shown that the soils of the mountain region are susceptible to flood processes Key words: morphology, association, section, horizon, granulometry